Practice Patterns in the Treatment and Monitoring of Acute T Cell–Mediated Kidney Graft Rejection in Canada. Issue 1 (15th February 2018) - Leblanc, Julie; Subrt, Peter; Paré, Michèle; Hartell, David; Sénécal, Lynne; Blydt-Hansen, Tom; Cardinal, Héloïse
Background: One of the goals of the Canadian National Transplant Research Program (CNTRP) is to develop novel therapies for acute rejection that could positively affect graft outcomes with greater efficacy or less toxicity. To develop innovative management strategies for kidney graft rejection, new modalities need to be compared with current clinical practices. However, there are no standardized practices concerning the management of acute T cell–mediated rejection (TCMR). Objectives: To describe clinicians' practice patterns in the diagnosis, treatment, and monitoring of acute TCMR in Canada. Design: Survey. Setting, Patients/Participants: Canadian transplant nephrologists and transplant surgeons involved in the management of acute TCMR. Methods and Measurements: We developed an anonymous, web-based survey consisting of questions related to the diagnosis, treatment, and monitoring of TCMR. The survey was disseminated on 3 occasions between June and October 2016 through the Canadian Society of Transplantation (CST) kidney group electronic mailing list. Results: Forty-seven respondents, mostly transplant nephrologists (97%), originating from at least 18 of the 25 Canadian centers offering adult or pediatric kidney transplantation, participated in the study. Surveillance biopsies were used by 28% of respondents to screen for kidney graft rejection. High-dose steroids were used by most of the respondents to treat clinical and subclinical Banff grade 1A and 1B rejections. Nine percent (95% confidence interval [CI]: 1-17) of practitioners used lymphocyte-depleting agents as the first-line approach for the treatment of Banff grade 1B acute rejection. Eighteen percent (95% CI: 7-29) and 36% (95% CI: 8-65) of respondents reported that they would not use high-dose steroids for treating clinical and subclinical borderline rejections, respectively. Seventy percent (95% CI: 54-83) of respondents answered that there was no indication to assess histological response to treatment independent of the change in kidney function. Limitations: The limitations of this study are its limited sample size and the low representation of pediatric specialists. Conclusions: There is heterogeneity regarding the use of surveillance biopsies, treatment of borderline rejection, and modalities to monitor treatment response among transplant physicians. Our results illustrate the current state of practice patterns across Canada and can be used to inform the design of future trials.